Influence of milled and acid-treated graphene oxide on the self-healing properties of graphene oxide reinforced polyurethane - Kim, Hyeongtae; Lee, Jihyun; Shim, Soo Bin; Kim, Moon Se; Shrimant, Bharat; Lee, Jae Hyun; Nam, Sang Yong; Kwon, Dong Jun; Park, Jun Hong (Composites Part B: Engineering, 2023)
The presence of microcracks in polymer coatings degrades the structural stability and lifespan of the protective layers. Enhancing the polymer-coated surfaces with self-healing properties has attracted considerable attention as it increases the reliability and lifespan of polymer systems. Herein, the strength and self-healing properties of polyurethane/graphene oxide (PU/GO) composite materials were improved using two GO treatments, referring to mechanical milling and chemical treatment with HF. When GO was surface treated for 5 h with an HF concentration of 40%, and PU/GO was heated 80 °C for 6–8 h, the over 80% healing efficiency can be obtained. The HF-treated GO-reinforced composites demonstrated high self-healing efficiency and remarkable mechanical performance, making them a promising self-healing material for protecting structural composites.
Keywords: Acid treated; Graphene oxides; Lifespans; Polymer coated surfaces; Polymer Coating; Polymer composite; Protective layers; Self-healing; Self-healing properties; Structural stabilities; Graphene oxide; Polymer composite; Polyurethane; Self-healing